Process automation strategy in services, manufacturing and construction - Mohapatra, Bharati; Mohapatra, Sanjana; Mohapatra, Sanjay (Emerald Publishing Limited, 2023)
The importance of automation in the various industries has increased dramatically in recent years; business process automation serves to enhance product quality, improve process safety and plant availability, and efficiently utilize resources and lower emissions. With almost every industry facing sweeping and unprecedented change, Process Automation Strategy in Services, Manufacturing and Construction responds to a rapid pace of transformation that is both a major challenge and a fantastic opportunity. Customers' expectations grow higher, economic pressures require them to do more with less, and each day new competitors appear. Examining case studies and examples of robotic process automation (RPA) across a range of industries and sectors, the authors explore the links between customer satisfaction and organizational performance, and how automation improves service for the end user. Appealing to business researchers, academics and practitioners, Process Automation Strategy in Services, Manufacturing and Construction brings to life the current trends in process automation and considers what the future holds.